Citra Perempuan Minangkabau dalam Kaba Bujang Piaman jo Puti Payuang Lauik Versi Selasih - Andriani, Nini; WS, Hasanuddin; Nst., M. Ismail (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article was aimed to describe and analyze dialogues or monologues which reflected the image of Minangkabauâ€™s women which written in â€œkabaâ€ Bujang Piaman jo Puti Payuang lauik by Selasih version. The data of this research was taken from dialogues or monologues which reflected the image of Minangkabauâ€™s women in â€œkabaâ€. Sources of the data was dialogues or monologues written in â€œkabaâ€. These data was collected by using descriptive method and collection teachnigue: comprehensive reading of the story, determining the main character, and identifying the main characterâ€™s behaviour which considered as the data of Minangkabauâ€™s women of reflection. This research found that: (1) womenâ€™s reflection was as a personality, and (2) womenâ€™s reflection was a civil society.